The Environmental Implications of Privatization : Lessons for Developing Countries - Lovei, Magda; Gentry, Bradford S. (Washington, DC: World Bank, 2013)
Governments worldwide have increasingly recognized the economic potential and fiscal advantages of privatization. What is less well recognized is that, under the right conditions, privatization can also yield environmental benefits and contribute to sustainable development. This report reviews a number of case studies to draw lessons about the environmental implications of privatization. It emphasizes that privatization offers an opportunity for making strategic decisions with longer-term impacts; streses that integrating environmental and social considerations into the privatization process leads to better, more sustainable outcomes; and recommends approaches to building on the positive linkages between privatization and environmental protection.